KOPI DALAM SEJUMLAH RESENSI SASTRA DI KORAN NASIONAL INDONESIA - Kusmarwanti, Kusmarwanti; Nurhadi, Nurhadi (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2020)
(Title: Coffee in a Number of Literary Reviews in Indonesian National Newspapers). This study attempts to (1) map the authors of literary work reviews published in the 2016-2018 national newspaper which raise coffee as their theme, and to (2) describe the readers' responses on the literary works. It is found that there are four reviews which examined some novels namely Ladu, Siti Kewe, Romansa Gayo dan Bordeaux, and a poem collection entitled Secangkir Kopi Sekanak. Reviews of these literary works were published in Republika, Media Indonesia, and Koran Tempo. The current study is a qualitative research using a literary reception approach. Readers' responses which were investigated in this study include literary work reviews. The result of this study is that the authors, who gave responses to the literary works, were literary enthusiasts and served as permanent writers in the aforementioned media (e.g.Nina Ch. in Republika, M-2 in Media Indonesia) or literary enthusiasts and worked as freelance writers (e.g. Chandra A., Ferdian Ananda Majni). Reviews in the newspaper were considered popular and oriented to providing information on newly-released books. This study also revealed that the readers' responses discuss coffee in relation to Gayo and Aceh, environmental issues, history, inner conflicts of the search for God, and the nature of coffee as a complement for solving life problems.Keywords: coffee, literary reviews, reception theory